THE ASSIMILATION CONSONANT SOUND PROCESS RESEMBLANCES BETWEEN ENGLISH AND BATAK LANGUAGE - Mangantar Sitohang (Journal of English Language and Literature (JELL), 2018)
This research attempts to describe Assimilation Consonant Sound Process Resemblances found in English and Batak Language, one of the local languages existing in Indonesia seen from Consonant Classifications Angles. Showing and describing the resemblance or similarity of assimilation process of the two languages can enrich our insight about this reality or process. Their resemblance discussed here is focused on utterance or oral communication/spoken language, precisely in accent level. As popularly known, in English, it is not always easy to know what sounds the letters stand for. The same letters often have some different sound symbols or patterns depending on their boundaries or environment. There are forty four (44) English sound symbols as the representation of 26 English letters, while in Batak language (especially Batak language variety/dialect in Samosir, from the 26 letters known, their sound symbols are also twenty six, more or less the same as the sound symbols found in Bahasa Indonesia. So in English, every written letter always reminds us of corresponding sound symbols when speaking, while in Batak Language those don’t exist. But what is unique and interesting the researcher always has in mind, although English and Batak Languages do have huge difference if seen from Linguistics, but at the same time they do have certain resemblances which can be shown/described from English assimilation process